Предмет: Алгебра,
автор: Енот980
Решите уравнение .
1 . ( 2x - 1 ) ² - 9x² = 0
2 . 5(x+2)²+(2x-1)²-9(x+3)(x-3)=22
Ответы
Автор ответа:
0
1 . ( 2x - 1 ) ² - 9x² = 0
(2x-1-3x)(2x-1+3x)=0
(-x-1)(5x-1)=0
-x-1=0
x=-1
5x-1=0
5x=1
x=1/5
2 . 5(x+2)²+(2x-1)²-9(x+3)(x-3)=22
5x²+20x+20+4x²-4x+1-9x²+81-22=0
16x=-80
x=-80:16
x=-5
(2x-1-3x)(2x-1+3x)=0
(-x-1)(5x-1)=0
-x-1=0
x=-1
5x-1=0
5x=1
x=1/5
2 . 5(x+2)²+(2x-1)²-9(x+3)(x-3)=22
5x²+20x+20+4x²-4x+1-9x²+81-22=0
16x=-80
x=-80:16
x=-5
Похожие вопросы
Предмет: Математика,
автор: avakotik89
Предмет: История,
автор: konovalova201006
Предмет: Алгебра,
автор: max283828
Предмет: Математика,
автор: klyuch7983